ANALISIS NILAI-NILAI PENDIDIKAN ISLAM DALAM FILM AJARI AKU ISLAM - Danti Oktalita T; Bustanur Bustanur; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2023)
This research is motivated by Islamic education which is not only studied through education benches, in terms of practice and its application in society, learning media is needed that is not only in the form of books, especially in today’s era, in practice and rituals, real examples are needed which are summarized through the film, one of them. The educational value of a film in uestion is in the from of messages and morals contained in the film. The film “Ajari Aku Islam” is a religious film from Indonesia that was released in 2019 based on the true story of a film producer, Jaymes Rianto. This film contains many islamic educational values that can be used as a reference for educatos and parents in educating their children. This study focuses on the values of Islamic education in the film Ajari Aku Islam. This reseaarch is a library research, which uses a non-field ualitative approach, the techniue used is content analysis. Data were obtained from each character’s dialogues and their actions related to the values of Islamic education in the film. Based on the research conducted, it shows the value of Islamic education contained in the film Ajari Aku Islam, namely the educational value of aidahtawhid, which includes faith in Qadha dan Qadar. The value of worship education which includes saying the two sentences of the creed and establishing prayer. The value of moral education which includes morality to God and morality to humans.